Developing professional communicative competence through the medium of the English language; 10th International Technology, Education and Development Conference (INTED2016), Valencia, Spain, 7-9 March, 2016 - Slesarenko I. V. Inga Valerievna; Abdrashitova M. O. Mariya Ovseevna; Mymrina D. F. Dina Fedorovna; Dorokhova M. Yu. Mariya Yurjevna; Astafjeva I. S. Inna Sergeevna (2016, 2016)
Title screen